The particle ma in Old Sundanese - Gunawan, Aditia; Fauziyah, Evi Fuji (UI Scholars Hub, 2021)
This article will analyse the distribution of the particle ma in Old Sundanese texts. Based on an examination of fifteen Old Sundanese texts (two inscriptions, eight prose texts, and five poems), we have identified 730 occurrences of ma. We have selected several examples which represent the range of its grammatical functions in sentences. Our observations are as follows: (1) ma not only appears in direct dialogues, but also in narrative texts, both prose and verse; (2) ma functions as a copula in nominal sentences, connecting subject and predicate; (3) in conditional clauses containing the conjunction lamun, ma has a function similar to that of mah in Modern Sundanese but, in the absence of lamun and if the supplementary clauses only consist of verb phrases, ma itself is also capable of expressing conditionality; (4) if this particle is preceded by negations such as hamo ‘not’ or hantə ‘there is not’ in conditional clauses, ma is placed directly after these negations and does not mark the predicate, but serves instead to stress the negation itself; (5) in the cases described in points 1-4, ma can be considered a topic marker, and in some phrases we have even found the dislocations that are characteristic of topic markers; and (6) ma can appear in imperative sentences, placed immediately after verbs to emphasize commands, which does not apply to mah in Modern Sundanese.